Bilateral Brachial Artery Disease Presenting with Features of Raynaud's Phenomenon: A Case Report and Review of the Literature. (10th July 2017) - Seegobin, Karan; Lyons, Brittany; Maharaj, Satish; Baldeo, Cherisse; Reddy, Pramod; Cunningham, James
Abstract : Objective . To present a case of bilateral brachial artery disease presenting with features of Raynaud's phenomenon which was successfully treated with angioplasty and stenting, together with a review of the relevant literature. Case . A 71-year-old female presented with a one-year history of intermittent pallor of both hands precipitated with cold objects. On examination, bilateral radial pulses were reduced. Prior photos showed pallor of the distal aspect of both palms. Angiogram showed high grade stenosis of the right brachial artery and focal occlusion with likely dissection of the left brachial artery. She underwent angioplasty and stenting for both lesions. She was asymptomatic without further episodes of Raynaud's phenomenon after five months on dual antiplatelet therapy. Upper-extremity vascular stenosis is uncommon. Structural changes in the vessel wall can cause vasospastic attacks, a mechanism described in secondary Raynaud's phenomenon. We hypothesize that these attacks may have been precipitated by the bilateral brachial artery disease. Furthermore, resolution of the symptoms after stent further supports our theory. Conclusion . Bilateral brachial artery disease is uncommon. Physicians should consider this in patients presenting with Raynaud's phenomenon. Brachial artery stenosis and occlusion is a treatable disease with good symptomatic outcomes after angioplasty and stenting.